TOLERANSI MASAM Vitex pubescens VAHL. IN -VITRO DAN EX-VITRO - Asri Insiana Putri (Jurnal Pemuliaan Tanaman Hutan, 2010)
This study aims to observe acid tolerance of Vitex pubescens culture growth. Planlet cultures were established from seeds on Murashige & Skoog medium supplemented with 1 µM benzylaminopurin; 0,1 µM kinetin and 0,01 µM naphtalenaceticacid. The pH was adjusted to 5,7;4,0 and 3,0. The mean height of planet were 4,44 cm ± 0,32 for pH 5,7; 2,88 cm ± 0,54 for pH 4 and 1,10 cm ± 1,38 for pH 3. The mean length of root were 13,72 cm ± 0,47 for pH 5,7; 18,88 cm ± 0,60 for pH  and 19,27 cm ± 0,73 pH 3. The mean number of branch roots per cm were 1,65 ± 0,058 for pH 5,7;3,88 ± 0,18 for pH 4 and 0,57 ± 0,30 for pH. After 12 weeks acclimatization in Yellow Red Podzolic (YRP) soil, the mean height of plant with pH 5,7 culture were 29,86 cm ± 0,64 and 26,72 cm ± 0,40 for pH culture. In vitro acid tolerance of Vitex pubescens were at pH 4 and can grow in ex vitro condition in YRP soil with pH 4,48.